2004
DOI: 10.1108/10650750410564682
|View full text |Cite
|
Sign up to set email alerts
|

The electronic library: responses from the State University of New York (SUNY)

Abstract: Illustrates the methods of pointing to remotely‐accessible electronic resources in libraries in a university system ranging from research centers to community colleges. The online catalogs of libraries in the State University of New York (SUNY) system were tested for remotely‐accessible electronic resources. Each library's internet home page was also searched for means of linking to journal titles. The libraries at SUNY campuses have shown different responses to the issues of making available aggregator databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…There are studies discussing cataloguing of electronic resources, especially focusing on metadata issues. Access to electronic resources through the library's online catalogue is discussed by Joseph Petrick (2004) for which cataloguing of electronic resources is necessary. Experience of cataloguing of electronic resources at the University of Albany libraries using 360 MARC implementation was shared by Nous and West (2015) whereas changing cataloguing workflow at the University of Maryland was discussed by Guay and King (2014).…”
Section: Review Of Literaturementioning
confidence: 99%
“…There are studies discussing cataloguing of electronic resources, especially focusing on metadata issues. Access to electronic resources through the library's online catalogue is discussed by Joseph Petrick (2004) for which cataloguing of electronic resources is necessary. Experience of cataloguing of electronic resources at the University of Albany libraries using 360 MARC implementation was shared by Nous and West (2015) whereas changing cataloguing workflow at the University of Maryland was discussed by Guay and King (2014).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Another study by Nelson (2008) showed that both students and faculty generally favor e‐books more than printed books in research but neither of them are very enthusiastic about using e‐textbooks in classroom. As corroborated by Petrick (2004), electronic library resources such as e‐books and e‐journals are easier to organize than printed resources.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of the internet‐use themes that have been explored in academic environments have included the use of the internet for e‐mail (Adika, 2003; Applebee et al , 2000; Oduwale, 2004); the use of the internet for communication with friends and relatives (Luambano and Nawe, 2004); the use of the internet as a virtual referencing tool (Song, 2004; Devlin and Burke, 1997); and data integrity issues in respect of the use of the internet for academic purposes (Mathieu and Woodard, 1996). Other themes that have been explored in respect of internet use in academic environments have also included the use of the internet for research‐related activities (Tingling et al , 2003), and the internet as a tool, or improving the delivery of library services (Younis, 2002; Siddiqui, 2003a, b), and the internet as a source of academic databases and e‐books (Vicente et al , 2004; Petrick, 2004). These scattered and varying uses of the internet do not present a holistic enough picture of the widest ranges to which an academic can put the internet in an effort to maximize his/her productivity.…”
Section: The Research Gapmentioning
confidence: 99%